A multi-component composite coating and its preparation process
By adding functional additives and cracking enhanced agents to epoxy resin coatings to form multi -component composite coatings, the problem of cracking of epoxy resin coatings during expansion and contraction, and improved waterproof performance and wear resistance. Extend the service life.
Patent Information
- Application Number
- CN202311568721.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-11-23
AI Technical Summary
Epoxy resin coatings are prone to cracking during expansion and contraction, resulting in weakening of waterproofing effect, and their water resistance is poor and their service life is short.
Multiple component composite coatings formulas include epoxy resin base materials, functional additives (polytendene derivatives containing fluorosilicid hydrophilic chain segments in the structure), cracking agent (polyether polyol and carboxymethyl fiber fiber Primrose connection complexes), etc., improve the waterproof performance and abrasion resistance of the coating through chemical connection and physical cross -linking.
The waterproof performance of epoxy resin coatings is achieved, the coating has a super hydration effect, the abrasion resistance and flexibility have also been improved, thereby extending the service life.
Smart Images

Figure CN117511340B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a multi-component composite coating and a preparation process thereof. Background Art
[0002] With the rapid development of modernization, building waterproof materials have received more and more attention. At present, the common waterproof materials are mainly waterproof membranes and waterproof coatings. However, waterproof membranes need to be customized and cut according to the shape of the base layer, which makes construction difficult. In addition, waterproof membranes are difficult to bond and cannot be completely sealed, which greatly increases the risk of water leakage. In addition, the maintenance of waterproof membranes after construction is more difficult, which leads to the gradual elimination of waterproof membranes in modern buildings. In comparison, waterproof coatings are easy to construct and can form a dense coating after curing, showing good waterproofing effect.
[0003] Waterproof coatings include polymer-based coatings, cement-based coatings, asphalt, tar, etc. Cement-based coatings have strong permeability and poor waterproofing effect. Asphalt, tar, etc. contain harmful substances and are not environmentally friendly, so it is difficult to meet the needs of practical applications. Polymer-based coatings have good film-forming properties and have been widely used in the field of waterproof coatings in recent years. Epoxy resin coatings have excellent anti-corrosion and anti-mildew properties and can be used to make waterproof coatings. However, most buildings are cement-based. Cement is easy to expand when heated and easy to shrink when cold. This causes the waterproof coating to crack easily during the expansion and contraction process, causing the waterproof effect to be greatly weakened. At the same time, the water resistance of epoxy resin itself is poor. Long-term rainwater infiltration will also greatly reduce the service life of epoxy resin coatings. Therefore, epoxy resin waterproof coatings need to be improved in practical applications.
[0004] The invention patent with application number CN202210730733.5 discloses a method for preparing a ternary composite resin and its waterproof coating. Hydrogenated epoxy resin, hydroxyl acrylic resin and silicone resin are used as raw materials, chemically connected to form a ternary composite resin, and then mixed with other additives to prepare a waterproof coating with excellent performance. Therefore, by optimizing the structure of the epoxy resin, the purpose of modifying the epoxy resin coating can be achieved. Summary of the invention
[0005] The purpose of the present invention is to provide a multi-component composite coating and a preparation process thereof, which solves the problem that the epoxy resin coating has a poor waterproof effect.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A multi-component composite coating, comprising the following raw materials by weight: 45-60 parts of epoxy resin base material, 15-25 parts of functional additives, 2-6 parts of anti-cracking enhancer, 0.5-1 parts of thixotropic agent, 10-15 parts of pigments and fillers, 5-10 parts of diluents, 0.1-0.5 parts of defoaming agents, and 20-30 parts of curing agents;
[0008] The functional additive is a polybutadiene derivative containing a fluorine-silicon hydrophobic segment in its structure;
[0009] The anti-cracking enhancer is a grafted composite of polyether polyol and carboxymethyl cellulose.
[0010] Furthermore, the epoxy resin base material is any one of bisphenol A epoxy resin or bisphenol F epoxy resin; the thixotropic agent is fumed silica; the color filler is any one of titanium dioxide or calcium carbonate; the diluent is any one of ethyl carbonate, dimethyl adipate or dimethyl pentanecarboxylate; the defoamer is any one of BYK-052N or BYK-085; and the curing agent is any one of polyetheramine or hexamethylenediamine.
[0011] Furthermore, the preparation method of the functional additive comprises the following steps:
[0012] Step S1: mixing epoxidized hydroxyl-terminated liquid polybutadiene with toluene, adding allyldimethylsilyl chloride and triethylamine, starting stirring, introducing nitrogen, keeping the temperature at 60-70° C. for 4-6 hours, evaporating the solvent, cooling and discharging the material to obtain an intermediate material;
[0013] Step S2: putting the intermediate material, hydrogen-containing silicone oil, fluorine-containing unsaturated monomer and N,N-dimethylformamide into a reaction kettle, stirring and mixing evenly, passing nitrogen to deoxygenate, adding chloroplatinic acid, raising the temperature to 90-100° C., stirring at a constant temperature for 8-12 hours, evaporating the solvent, discharging the material, and obtaining a functional additive.
[0014] In the above technical scheme, the terminal hydroxyl group in the structure of the epoxidized terminal hydroxyl liquid polybutadiene can be replaced with the Si-Cl in the structure of the allyldimethylchlorosilane under the action of triethylamine to obtain an epoxidized terminal olefinic liquid polybutadiene intermediate material. The Si-H in the structure of the hydrogen-containing silicone oil is used as a bridge, and under the catalysis of chloroplatinic acid, an addition reaction occurs with the intermediate material and the olefinic group in the structure of the fluorine-containing unsaturated monomer to obtain a functional additive containing a fluorine-containing segment, silicone oil and epoxidized polybutadiene in the structure.
[0015] Furthermore, in step S1, the epoxy value of the epoxidized hydroxyl-terminated liquid polybutadiene is 1.7-2 mmol / g.
[0016] Furthermore, in step S2, the hydrogen content of the hydrogen-containing silicone oil is 0.5%.
[0017] Furthermore, in step S2, the fluorine-containing unsaturated monomer is any one of hexafluorobutyl acrylate, hexafluorobutyl methacrylate or octafluoropentyl methacrylate.
[0018] Furthermore, the preparation method of the anti-cracking enhancer comprises the following steps:
[0019] Step SS1: mix sodium carboxymethyl cellulose, p-toluenesulfonic acid and dimethyl sulfoxide, keep stirring at 50-60° C. for 20-40 min, filter out the solid material, and obtain carboxymethyl cellulose;
[0020] Step SS2: Mix polyether polyol, carboxymethyl cellulose and chloroform, stir to mix, then add the composite catalyst, after adding, stir at room temperature for 12-18 hours under nitrogen protection, separate the solid material, wash and vacuum dry to obtain the anti-cracking enhancer.
[0021] In the above technical scheme, sodium carboxymethyl cellulose is protonated with p-toluenesulfonic acid to convert -COONa into -COOH to obtain a carboxymethyl cellulose solution. Under the action of a composite catalyst, the terminal hydroxyl groups in the polyether polyol structure can undergo dehydration condensation with the -COOH in the carboxymethyl cellulose structure to obtain a grafted composite of polyether polyol and carboxymethyl cellulose, i.e., an anti-cracking enhancer.
[0022] Furthermore, in step SS2, the functionality of the polyether polyol is 3, the average molecular weight is 4000, and the hydroxyl value is 40-44 mg KOH / g.
[0023] Furthermore, in step SS2, the composite catalyst is a composite of N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, with a mass ratio of 1:0.05-0.1.
[0024] A preparation process of a multi-component composite coating comprises the following steps:
[0025] Step 1: Weigh each raw material according to weight and set aside;
[0026] Step 2: Pour the epoxy resin base material, functional additives, anti-cracking enhancer, thixotropic agent, pigment and filler and diluent into a stirring kettle, stir and mix, add the defoamer, continue stirring for 20-30 minutes, stand and defoam to obtain a premix;
[0027] Step 3: Add curing agent to the premix, stir mechanically to make it uniform, and store it at room temperature to obtain a composite coating.
[0028] Beneficial effects of the present invention:
[0029] 1) The present invention prepares a functional additive containing a fluorine-containing segment, silicone oil and epoxidized polybutadiene in the structure, and mixes it with additives such as epoxy resin base materials. During the curing process, the epoxy group in the functional additive structure can participate in the curing reaction of the epoxy resin base material, thereby introducing silicone oil and fluorine-containing segments into the epoxy resin structure, and utilizing the low surface activity of silicone oil and fluorine-containing segments to make the coating formed by curing the epoxy resin composite coating have extremely low surface energy, produce a super-hydrophobic effect, and effectively improve the waterproof performance of the composite coating. In addition, the presence of silicone oil can improve the wear resistance of the coating, and the presence of polybutadiene can improve the flexibility of the coating, thereby greatly increasing the service life of the coating.
[0030] 2) The present invention strengthens the epoxy resin composite coating by preparing an anti-cracking enhancer. The macromolecular cellulose in the structure of the anti-cracking enhancer can form a large number of hydrogen bonds with the epoxy resin, producing a physical cross-linking effect, making the coating formed by curing the composite coating more compact and effectively preventing the penetration of water. In addition, the macromolecular cellulose can play an "anchoring" role, and the polyether structure can produce a role similar to "capillary fibers". When the coating formed by curing the composite coating is expanded or contracted, the stress cracking of the coating can be effectively prevented through the pulling effect of the "capillary fibers". Moreover, the polyether segment in the structure of the anti-cracking enhancer can also improve the adhesion between the composite coating and the adhered substrate, which is conducive to further broadening the application scope of the composite coating.
[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0033] Figure 1 This is an infrared characterization diagram of the functional additive of the present invention;
[0034] Figure 2 This is an infrared characterization diagram of the anti-cracking enhancer of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The functional additives used in the following examples and comparative examples were prepared by the following method:
[0037] Step S1: 3.5 g of epoxidized hydroxyl-terminated liquid polybutadiene having an epoxy value of 2 mmol / g is mixed with toluene, 0.8 g of allyldimethylsilyl chloride and 0.5 g of triethylamine are added, stirring is started, nitrogen is introduced, and the mixture is kept at 65° C. for 6 h, the solvent is evaporated, the temperature is lowered, and the material is discharged to obtain an intermediate material;
[0038] Step S2: 2.8 g of the intermediate material, 1.2 g of hydrogen-containing silicone oil with a hydrogen content of 0.5%, 0.5 g of hexafluorobutyl acrylate and N,N-dimethylformamide are put into a reaction kettle, stirred and mixed evenly, nitrogen is passed to deoxygenate, 0.001 g of chloroplatinic acid is added, the temperature is increased to 95° C., and after constant temperature stirring for 9 hours, the solvent is evaporated, the material is discharged, and a functional additive is obtained.
[0039] Figure 1 This is the infrared characterization image of the functional additive. The analysis shows that 3021cm -1 The peak of CH stretching vibration in carbon-carbon double bond, 1327cm -1 and 1302cm -1 CF stretching vibration peak, 1250cm -1 Si-C stretching vibration peak, 1115 cm -1 Si-O-Si stretching vibration peak, 1089cm -1 Si-OC stretching vibration peak, 895 cm -1 It is the characteristic absorption peak of epoxy group.
[0040] The anti-cracking reinforcing agent used in the following examples and comparative examples was prepared by the following method:
[0041] Step SS1: 5 g of sodium carboxymethyl cellulose, 2 g of p-toluenesulfonic acid and dimethyl sulfoxide were mixed, stirred at 55° C. for 30 min, and solid materials were filtered out to obtain carboxymethyl cellulose;
[0042] Step SS2: 1.6 g of a polyether polyol having a functionality of 3, an average molecular weight of 4000, and a hydroxyl value of 40 mg KOH / g, 4.2 g of carboxymethyl cellulose and chloroform are mixed and stirred, and then 0.6 g of N,N'-dicyclohexylcarbodiimide and 0.05 g of 4-dimethylaminopyridine are added. After the addition is completed, the mixture is stirred at room temperature for 16 hours under nitrogen protection, and the solid material is separated, washed, and vacuum dried to obtain an anti-cracking enhancer.
[0043] Figure 2 This is the infrared characterization diagram of the anti-cracking enhancer. The analysis shows that 3392cm -1 OH stretching vibration peak, 1755 cm-1 The C=O stretching vibration peak in the ester group, 1708 cm -1 The C=O stretching vibration peak of the carboxyl group in carboxymethyl cellulose that does not participate in the reaction, 1142 cm -1 It is the stretching vibration peak of ether bond. Example 1
[0044] A multi-component composite coating, comprising the following raw materials by weight: 45 parts of E51 epoxy resin base material, 15 parts of functional additives, 2 parts of anti-cracking enhancer, 0.5 parts of fumed silica, 10 parts of titanium dioxide, 5 parts of ethyl carbonate, 0.1 parts of defoamer BYK-052N, and 20 parts of hexamethylenediamine;
[0045] The preparation method of the composite coating comprises the following steps:
[0046] Step 1: Weigh each raw material according to weight and set aside;
[0047] Step 2: Pour E51 epoxy resin base material, functional additives, anti-cracking enhancer, fumed silica, titanium dioxide and ethyl carbonate into a stirring kettle, stir and mix, add defoamer BYK-052N, continue stirring for 20 minutes, stand and defoam to obtain a premix;
[0048] Step 3: Add hexamethylenediamine to the premix, stir evenly mechanically, and store at room temperature to obtain a composite coating. Example 2
[0049] A multi-component composite coating, comprising the following raw materials by weight: 55 parts of E51 epoxy resin base material, 24 parts of functional additives, 5 parts of anti-cracking enhancer, 0.6 parts of fumed silica, 12 parts of calcium carbonate, 6 parts of dimethyl adipate, 0.3 parts of defoamer BYK-085, and 25 parts of hexamethylenediamine;
[0050] The preparation method of the composite coating comprises the following steps:
[0051] Step 1: Weigh each raw material according to weight and set aside;
[0052] Step 2: Pour E51 epoxy resin base material, functional additives, anti-cracking enhancer, fumed silica, calcium carbonate and dimethyl adipate into a stirring kettle, stir and mix, add defoamer BYK-085, continue stirring for 25 minutes, stand and defoam to obtain a premix;
[0053] Step 3: Add hexamethylenediamine to the premix, stir evenly mechanically, and store at room temperature to obtain a composite coating. Example 3
[0054] A multi-component composite coating, comprising the following raw materials by weight: 60 parts of E51 epoxy resin base material, 25 parts of functional additives, 6 parts of anti-cracking enhancer, 1 part of fumed silica, 15 parts of calcium carbonate, 10 parts of dimethyl pentanedicarboxylate, 0.5 parts of defoamer BYK-085, and 30 parts of hexamethylenediamine;
[0055] The preparation method of the composite coating comprises the following steps:
[0056] Step 1: Weigh each raw material according to weight and set aside;
[0057] Step 2: Pour E51 epoxy resin base material, functional additives, anti-cracking enhancer, fumed silica, calcium carbonate and dimethyl pentanecarboxylate into a stirring kettle, stir and mix, add defoamer BYK-085, continue stirring for 30 minutes, stand and defoam to obtain a premix;
[0058] Step 3: Add hexamethylenediamine to the premix, stir evenly mechanically, and store at room temperature to obtain a composite coating.
[0059] Comparative Example 1
[0060] A multi-component composite coating, comprising the following raw materials by weight: 55 parts of E51 epoxy resin base material, 24 parts of epoxidized hydroxyl-terminated polybutadiene, 5 parts of anti-cracking enhancer, 0.6 parts of fumed silica, 12 parts of calcium carbonate, 6 parts of dimethyl adipate, 0.3 parts of defoamer BYK-085, and 25 parts of hexamethylenediamine;
[0061] The preparation method of the composite coating comprises the following steps:
[0062] Step 1: Weigh each raw material according to weight and set aside;
[0063] Step 2: Pour E51 epoxy resin base material, epoxidized hydroxyl-terminated polybutadiene, anti-cracking enhancer, fumed silica, calcium carbonate and dimethyl adipate into a stirring kettle, stir and mix, add defoamer BYK-085, continue stirring for 25 minutes, stand and defoam to obtain a premix;
[0064] Step 3: Add hexamethylenediamine to the premix, stir evenly mechanically, and store at room temperature to obtain a composite coating.
[0065] Comparative Example 2
[0066] A multi-component composite coating, comprising the following raw materials by weight: 55 parts of E51 epoxy resin base material, 5 parts of anti-cracking enhancer, 0.6 parts of fumed silica, 12 parts of calcium carbonate, 6 parts of dimethyl adipate, 0.3 parts of defoamer BYK-085, and 25 parts of hexamethylenediamine;
[0067] The preparation method of the composite coating comprises the following steps:
[0068] Step 1: Weigh each raw material according to weight and set aside;
[0069] Step 2: Pour E51 epoxy resin base material, anti-cracking enhancer, fumed silica, calcium carbonate and dimethyl adipate into a stirring kettle, stir and mix, add defoamer BYK-085, continue stirring for 25 minutes, stand for defoaming, and obtain a premix;
[0070] Step 3: Add hexamethylenediamine to the premix, stir evenly mechanically, and store at room temperature to obtain a composite coating.
[0071] Comparative Example 3
[0072] A multi-component composite coating, comprising the following raw materials by weight: 55 parts of E51 epoxy resin base material, 24 parts of functional additives, 0.6 parts of fumed silica, 12 parts of calcium carbonate, 6 parts of dimethyl adipate, 0.3 parts of defoamer BYK-085, and 25 parts of hexamethylenediamine;
[0073] The preparation method of the composite coating comprises the following steps:
[0074] Step 1: Weigh each raw material according to weight and set aside;
[0075] Step 2: Pour E51 epoxy resin base material, functional additives, fumed silica, calcium carbonate and dimethyl adipate into a stirring kettle, stir and mix, add defoamer BYK-085, continue stirring for 25 minutes, stand and defoam to obtain a premix;
[0076] Step 3: Add hexamethylenediamine to the premix, stir evenly mechanically, and store at room temperature to obtain a composite coating.
[0077] Comparative Example 4
[0078] A multi-component composite coating, comprising the following raw materials by weight: 55 parts of E51 epoxy resin base material, 0.6 parts of fumed silica, 12 parts of calcium carbonate, 6 parts of dimethyl adipate, 0.3 parts of defoamer BYK-085, and 25 parts of hexamethylenediamine;
[0079] The preparation method of the composite coating comprises the following steps:
[0080] Step 1: Weigh each raw material according to weight and set aside;
[0081] Step 2: Pour E51 epoxy resin base material, fumed silica, calcium carbonate and dimethyl adipate into a stirring kettle, stir and mix, add defoamer BYK-085, continue stirring for 25 minutes, stand for defoaming, and obtain a premix;
[0082] Step 3: Add hexamethylenediamine to the premix, stir evenly mechanically, and store at room temperature to obtain a composite coating.
[0083] Performance Testing
[0084] A. Refer to the national standard GB / T 9286-2021 for adhesion test; refer to the national standard GB / T 1768-2006 for abrasion resistance test; refer to the national standard GB / T 1731-2020 for flexibility test; refer to the national standard GB / T 1733-1993 for water resistance test. The test results are recorded in the following table:
[0085]
[0086] B. The composite coatings prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 are uniformly coated on the surface of tinplate, the thickness of the coating is controlled to be 45±5 um, and the coatings are placed in an oven at 80° C. for complete curing. The water contact angle of the coatings is tested using a PZ-200SD contact angle tester, and the test results are recorded in the following table:
[0087]
[0088] C. The composite coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention were uniformly coated on the surface of one side of the concrete block, and the thickness of the coating was controlled to be 100±5um. After being completely cured in an oven at 80°C, the concrete block was heated to 40°C and kept for 3 days. After that, the concrete block was placed at -5°C for 3 days. The concrete block was taken out and observed to see whether cracks occurred on the coating surface. If cracks occurred, it was recorded as a failure, otherwise it was recorded as a pass. The crack resistance of the coating was evaluated, and the test results were recorded in the following table:
[0089]
[0090] Based on the above test results, it can be seen that the composite coatings prepared in Examples 1 to 3 of the present invention have strong adhesion, and the coatings formed by curing have good wear resistance, flexibility, water resistance and crack resistance. In addition, they also have a super hydrophobic surface and can be used as a waterproof coating with excellent comprehensive performance.
[0091] The composite coating prepared in Comparative Example 1 uses epoxidized hydroxy-terminated polybutadiene as a functional additive, so that the prepared epoxy resin composite coating does not contain silicone oil and fluorine-containing segments, resulting in decreased wear resistance and water resistance, and does not have a super-hydrophobic surface.
[0092] The composite coating prepared in Comparative Example 2 does not contain any functional additives, and its flexibility also decreases to a certain extent compared with Comparative Example 1, indicating that epoxidized polybutadiene can improve the flexibility of the composite coating.
[0093] The composite coating prepared in Comparative Example 3 did not add an anti-cracking enhancer. Compared with the examples, the adhesion was reduced to a certain extent and the anti-cracking performance was poor.
[0094] The composite coating prepared in Comparative Example 4 not only does not add functional additives, but also does not add anti-cracking enhancers, so all performances are the worst.
[0095] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A multi-component composite coating, characterized in that: The following raw materials are included by weight: 45-60 parts of epoxy resin base material, 15-25 parts of functional additives, 2-6 parts of anti-cracking enhancer, 0.5-1 parts of thixotropic agent, 10-15 parts of pigments and fillers, 5-10 parts of diluent, 0.1-0.5 parts of defoamer, and 20-30 parts of curing agent; The functional additive is a polybutadiene derivative containing a fluorine-silicon hydrophobic segment in its structure; The preparation method of the functional additive comprises the following steps: Step S1: mixing epoxidized hydroxyl-terminated liquid polybutadiene with toluene, adding allyldimethylsilyl chloride and triethylamine, starting stirring, introducing nitrogen, keeping the temperature at 60-70° C. for 4-6 hours, evaporating the solvent, cooling and discharging the material to obtain an intermediate material; Step S2: putting the intermediate material, hydrogen-containing silicone oil, fluorine-containing unsaturated monomer and N,N-dimethylformamide into a reaction kettle, stirring and mixing evenly, passing nitrogen to deoxygenate, adding chloroplatinic acid, raising the temperature to 90-100° C., stirring at a constant temperature for 8-12 hours, evaporating the solvent, discharging the material, and obtaining a functional additive; The anti-cracking enhancer is a grafted composite of polyether polyol and carboxymethyl cellulose; The preparation method of the anti-cracking enhancer comprises the following steps: Step SS1: mix sodium carboxymethyl cellulose, p-toluenesulfonic acid and dimethyl sulfoxide, keep stirring at 50-60° C. for 20-40 minutes, filter out the solid material, and obtain carboxymethyl cellulose; Step SS2: Mix polyether polyol, carboxymethyl cellulose and chloroform, stir to mix, then add the composite catalyst, after adding, stir at room temperature for 12-18 hours under nitrogen protection, separate the solid material, wash and vacuum dry to obtain the anti-cracking enhancer.
2. A multi-component composite coating according to claim 1, characterized in that: The epoxy resin base material is any one of bisphenol A epoxy resin or bisphenol F epoxy resin; the thixotropic agent is fumed silica; the color filler is any one of titanium dioxide or calcium carbonate; the diluent is any one of ethyl carbonate, dimethyl adipate or dimethyl pentanecarboxylate; the defoamer is any one of BYK-052N or BYK-085; and the curing agent is any one of polyetheramine or hexamethylenediamine.
3. A multi-component composite coating according to claim 1, characterized in that: In step S1, the epoxy value of the epoxidized hydroxyl-terminated liquid polybutadiene is 1.7-2 mmol / g.
4. A multi-component composite coating according to claim 1, characterized in that: In step S2, the hydrogen content of the hydrogen-containing silicone oil is 0.5%.
5. A multi-component composite coating according to claim 1, characterized in that: In step S2, the fluorine-containing unsaturated monomer is any one of hexafluorobutyl acrylate, hexafluorobutyl methacrylate or octafluoropentyl methacrylate.
6. A multi-component composite coating according to claim 1, characterized in that: In step SS2, the functionality of the polyether polyol is 3, the average molecular weight is 4000, and the hydroxyl value is 40-44 mg KOH / g.
7. A multi-component composite coating according to claim 1, characterized in that: In step SS2, the composite catalyst is a composite of N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, with a mass ratio of 1:0.05-0.
1.
8. The process for preparing a multi-component composite coating according to claim 1, characterized in that: The following steps are involved: Step 1: Weigh each raw material according to weight and set aside; Step 2: Pour the epoxy resin base material, functional additives, anti-cracking enhancer, thixotropic agent, pigment and filler and diluent into a stirring kettle, stir and mix, add the defoamer, continue stirring for 20-30 minutes, stand and defoam to obtain a premix; Step 3: Add curing agent to the premix, stir mechanically to make it uniform, and store it at room temperature to obtain a composite coating.
Citation Information
Patent Citations
A method for preparing a ternary composite resin and its waterproof coating
CN115010937B
Synthesis method for polymer acrylate resin with photosensitive self-catalytic activity
CN109369881A
Two-component normal temperature non-curing asphalt polyurethane waterproof coating and preparation method thereof
CN110527424A